Al-Ibdāʻ al-Manhajī li al-ʻAql al-Muslim Dirāsah li al-Tawjīh al-Islām li Manāhij al-ʻUlūm al-Ijtimāʻiyyah - Nabil al-Samalluthy (Al-Zahra : Journal for Islamic and Arabic Studies, 2003)
There is a difference in perspective between Islam and the West about Scientific method. This is in contrast to the Western efforts to frame science in materialistic frame. This paper describes the main frame of the Muslim intellectual thought in the methods of social sciences. In this discussion, the authors divide it into several sub discussion, such as: Islamic perspective on the methodology of thinking; vision, mission and methodology limits in social sciences; revelation as the basis of epistemology of the social sciences, the reality of the social laws that rely on revelation, and the primacy of Islamic values toward the methodology for the study of social sciences.